2006
DOI: 10.1002/gcc.20321
|View full text |Cite
|
Sign up to set email alerts
|

Association of 11q loss, trisomy 12, and possible 16q loss with loss of imprinting of insulin‐like growth factor–II in Wilms tumor

Abstract: We evaluated the WT1 and IGF2 status and performed chromosome and/or comparative genomic hybridization analysis in 43 tumor samples from patients with Wilms tumor. On this basis, we classified them into 4 groups: WT1 abnormality, loss of heterozygosity (LOH) of IGF2, loss of imprinting (LOI) of IGF2, and retention of imprinting (ROI) of IGF2, which were seen in 12%, 30%, 16%, and 42% of the tumors, respectively. Patients in the LOI group were older than those in other groups (P < 0.01), and tumors in the WT1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 24 publications
2
31
1
Order By: Relevance
“…Interestingly, we found a very significantly average older age of diagnosis in WT patients with LOI, compared with both normally imprinted and LOH patients (Table 2), similar to previous reports (15,39). When we analyzed 11p15 LOI tumors with respect to their 11p13 LOI status, we found no significant difference in age of onset between WTs with and without 11p13 LOI.…”
Section: Loi At 11p15supporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we found a very significantly average older age of diagnosis in WT patients with LOI, compared with both normally imprinted and LOH patients (Table 2), similar to previous reports (15,39). When we analyzed 11p15 LOI tumors with respect to their 11p13 LOI status, we found no significant difference in age of onset between WTs with and without 11p13 LOI.…”
Section: Loi At 11p15supporting
confidence: 90%
“…Other studies have not consistently found an association between 11p15 LOI and 16q LOH (19,39,49), and in our results we saw an increased incidence of 16q LOH in 11p15 LOI WTs but this did not reach statistical significance (Table 2). Clearly, our comparison of the timing of LOH and LOI in WT progression (Fig.…”
Section: Loi In Wt Progressioncontrasting
confidence: 80%
“…(5,6) To detect IGF2 LOI, we used allelic expression analysis and/or a combination of COBRA of H19 DMR and SNP arrays. Both methods detected similar incidence of IGF2 LOI.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting reports on the rates of IGF2 LOI in Japanese with WTs; one study reported IGF2 LOI in none of 21 tumors, whereas we previously reported it in seven of 27 tumors. (5,6) These results prompted us to analyze the IGF2 imprinting status in a substantial number of Japanese children with WTs.Various abnormalities of the WT1 gene have been found in 13.0-17.6% of sporadic WTs. (7,8) WT1 is predominantly expressed in the embryonic kidney, and has a pivotal role in its development.…”
mentioning
confidence: 99%
See 1 more Smart Citation